Desenvolvimento de métodos analíticos para determinação de constituintes inorgânicos em solventes industriais - Rodrigues, Sabrina Poliana de França (Universidade Federal de São Carlos, 2023)
Controlling the content of inorganic constituents in solvents from industrial processes is necessary to monitor the process and meet the final product forecast. In this way, the calcination and digestion procedure assisted by microwave radiation was adequately offered for the determination of Fe, Cr and Ni in butyl acetate (butyl ethanoate – CAS 123-86-4) by plasma optical emission spectrometry. Inductively coupled (ICP OES). Recently, the Solvay Group found an opportunity to enter the pharmaceutical market by offering isopropyl alcohol (propan-2-ol – CAS 67-63-0), produced at the Paulínia plant, as an input for this segment. To meet this demand, a product sheet should contain a series of analyzes based on the methods of the American Pharmacopeia (USP, United States Pharmacopeia), including potential inorganic contaminants. In view of the above, a procedure was developed and validated for the determination of As, Cd, Co, Cr, Cu, Fe, Hg, Ni and Pb, which are some of the analytes that must be monitored in the isopropyl alcohol (propane-2) sample. -ol – CAS 67-63-0). To this end, alternatives for sample preparation and operational conditions for inductively coupled plasma optical emission spectrometry (ICP OES) determination were evaluated. Sample dilution in acidified aqueous medium and radiation microwave-assisted digestion were evaluated as sample preparation procedures. Regarding reliability methods, external reliability was evaluated based on an analytical curve in an acidified aqueous medium and the matrix compatibility method. The results obtained were statistically evaluated in relation to selectivity, linearity, accuracy and precision. The analytical methods presented included adequate linearity through the values of r and r2, the evaluation of residues and the homoscedasticity obtained for the majority of inorganic impurities in both proposed methods. The limit of detection and quantification of the curve meets the planned request (LOD < 0.1 mg L-1; LQ < 1.0 mg L-1).
Development of analytical methods for determining inorganic constituents in industrial solvents
Keywords: ICP OES; Solventes orgânicos; Constituintes inorgânicos; Inorganic constituents; Organic solvents; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE